Economic viability and selection of irrigation systems using simulation and stochastic dominance - Duenhas, Luiza Helena; Saad, João Carlos Cury [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2009)
In humid areas, irrigation systems are used to increase the crop yield. The selection of irrigation system to be used is a decision made under uncertainty. This paper shows a procedure that is an association between Monte Carlo simulation method and the criterion of Stochastic Dominance to analyze the viability and identify the best economic option under risk condition. To illustrate the applicability of the procedure, three types of irrigation systems are evaluated to be used in a citrus orchard in Sao Paulo State, Brazil. The irrigation systems evaluated are: drip, microirrigation, and traveling sprinkler. The decision indicator is the present value of net benefit associated with the increase of yield obtained with the irrigation system adopted. The Monte Carlo simulation method is used to generate the cumulative distribution of the present value for each one of the irrigation systems. These curves allow to analyze the economic viability of the three irrigation systems. According to the First Degree Stochastic Dominance, traveling sprinkler system was the best alternative with 95.7% probability of obtaining a positive present value. The second best option was the microirrigation with 82.7% and the worst result (57.3%) was obtained with drip irrigation.
Viabilidade econômica e seleção de sistemas de irrigação utilizando simulação e dominância estocástica
Keywords: Citrus; Economic viability; Irrigation systems; Simulation; Stochastic dominance